Compact, Polyvalent Mannose Quantum Dots as Sensitive, Ratiometric FRET Probes for Multivalent Protein–Ligand Interactions. (15th March 2016) - Guo, Yuan; Sakonsinsiri, Chadamas; Nehlmeier, Inga; Fascione, Martin A.; Zhang, Haiyan; Wang, Weili; Pöhlmann, Stefan; Turnbull, W. Bruce; Zhou, Dejian
Abstract: A highly efficient cap‐exchange approach for preparing compact, dense polyvalent mannose‐capped quantum dots (QDs) has been developed. The resulting QDs have been successfully used to probe multivalent interactions of HIV/Ebola receptors DC‐SIGN and DC‐SIGNR (collectively termed as DC‐SIGN/R) using a sensitive, ratiometric Förster resonance energy transfer (FRET) assay. The QD probes specifically bind DC‐SIGN, but not its closely related receptor DC‐SIGNR, which is further confirmed by its specific blocking of DC‐SIGN engagement with the Ebola virus glycoprotein. Tuning the QD surface mannose valency reveals that DC‐SIGN binds more efficiently to densely packed mannosides. A FRET‐based thermodynamic study reveals that the binding is enthalpy‐driven. This work establishes QD FRET as a rapid, sensitive technique for probing structure and thermodynamics of multivalent protein–ligand interactions. Abstract : Glycokonjugate : Dicht mit Mannose bedeckte Quantenpunkte (QDs) wurden mittels einer hocheffizienten Ligandenaustauschmethode hergestellt. Die Quantenpunkte wurden eingesetzt, um multivalente Wechselwirkungen von HIV/Ebola‐Rezeptoren (DC‐SIGN und DC‐SIGNR) mit einer schnellen und empfindlichen ratiometrischen Auslesestrategie auf Basis eines Förster‐Energietransfers zu untersuchen.